IMPROVING STUDENT'S WRITING SKILL THROUGH PROBLEM BASED LEARNING BY USING PICTURE ON DESCRIPTIVE TEXT - Kartikaningtyas, Annisa Prima; Ma'rifatulloh, Sayid (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This research aimed to improve the students’ skill in writing. It used Classroom Action Research (CAR). The method used by the researcher was problem-based learning by using picture. The Research subject were students’ of class VII A in SMPN 1 Sukorame consisting of 32 students. The Classroom Action Research was conducted 4 days on the date 12th, 15th, 16th and 17th August 2022. The researcher collected the data using test and observation sheet. After collecting the data, the researcher analyzed the data using the normality test and paired sample T-test. The results showed that there was a significant difference between the results of the pre-test and post-test. This can be seen from the average increase in pre-test and post-test scores, namely 56.28 for the pretest and 77.47 for the post-test. The use of problem-based learning by using picture in teaching writing can also improve the classroom situation in writing. In this case it can be seen the participation of students in the introductory part of the descriptive text, students listen and observe carefully and students do the exercises given with enthusiasm. Based on the paired samples test, it is known that sig. (2-tailed) 0.000, while alpha (α) 0.05 (0.000 < 0.05) means that Ho is rejected and Ha is accepted. In other words, the application of problem-based learning by using picture on descriptive text of students' writing skills increased.